Musicologist as translator : a case study on “The Classical Style: Haydn, Mozart and Beethoven” - Huang, Clement Hanlei (Nanyang Technological University, 2020)
The ability of musicologists to produce translations of quality, specifically in the English-Chinese language pair, is investigated here with a case study: a translation quality evaluation (TQE) on the first two chapters of Yang Yandi’s Chinese translation of Charles Rosen’s “The Classical Style: Haydn, Mozart and Beethoven”, using the Multi Quality Metrics (MQM) framework. “Quality” is defined using a Functionalist approach with respect to two specific end-user groups: academics and the general public. The data was gathered using the analytic method under the framework, comparing the ST and TT side-by-side. Four major dimensions: accuracy, logic, style and fluency were used to categorize the issues found. Out of a source text of 36,000 words and a target text of 75,000 words, 201 translation issues were observed. Accuracy was the dimension with the highest source of errors, totalling 59.2%. Detailed analysis was performed on the issues and it was found that most errors were linguistic-related. Issues concerning the usage of the TL were also observed. It is determined that the musicologist, while an expert in his own domain, could have been unfamiliar with the skillset of the translator. Collaborative efforts are recommended among musicologists and translators for future translation projects and academic research.